ANALISIS KESULITAN SISWA SMP DALAM MENYELESAIKAN SOAL CERITA PADA MATERI PERSAMAAN LINEAR SATU VARIABEL - Serina Serina; Gida Kadarisma; Heris Hendriana; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to find out what errors are experienced by students in solving story problems on one-variable linear equation material and what factors cause students to have difficulty working on problems on one-variable linear equation material. The type of research conducted is descriptive qualitative research method. The research subjects used were students of SMP Negeri in one of the Cimahi cities in class VII-J as many as 17 students. The data collection technique was carried out by giving a description test of 3 questions. The results of this study found that students' difficulties in solving story problems were lack of understanding of reading questions so that students did not write down what was known and asked, difficulty in compiling mathematical models, difficulty in determining completion results, using the wrong process, and difficulties in writing answers. end. The factors that cause students' difficulties in completing PLSV are not understanding the meaning of the question, not understanding the material for algebraic arithmetic operations, and students who are not accustomed to solving story problems.